Pengembangan Bahan Ajar Berorientasi Literasi Kearifan Lokal di Mas Al-Hikmah Soe Nusa Tenggara Timur - Syahrul Syahrul; Arifin Arifin; Amirulah Datuk; Farid Fauzi Almu; ST. Ramlah (Jurnal Pemberdayaan Masyarakat, 2019)
The low quality of education in MAS Al-Hikmah Soe shows that teachers are still lacking in the ability to develop teaching materials due to lack of training. Therefore, this program aims to develop teaching materials based on the local wisdom of the Timorese. In this community service, using a dialogical method that is carried out with training directly to the teachers and students. The result is (1) the teacher's response in this activity has a strong effect on their ability to develop teaching materials based on local wisdom, because they did not realize and know that the values of local wisdom can be used as material to develop teaching materials, but after participating in training they realize that teaching material is not difficult, because there are many around us that can be used as teaching material. (2) The teacher's paradigm for smartphones has changed after attending this training, because they consider smartphones to be dangerous to students, but after attending this training they realize that smartphones are the future of human civilization that cannot be resisted, precisely the applications in them can be used as online learning media.